Accuracy in discrimination of self-reported cooperators using static facial information - Little, A; Jones, B; DeBruine, L; Dunbar, R (2013)
People readily ascribe personality traits to others and believe that faces hold important guides to character. Here we examined the relationship between static facial appearance and self-reported cooperation/defection using the prisoner's dilemma (N=193). Study 1 combined face images of those self-reporting they would be most and least likely to cooperate. The composites of cooperators were seen as more cooperative than non-cooperators. Study 2 demonstrated accuracy with ratings of individual faces. Masculinity of face shape was negatively related to self-reported cooperation for men, but not women. Further, ratings of smile intensity were positively, but not significantly, related to self-reported cooperation. Overall, individuals appear able judge the potential of others to cooperate from static facial appearance alone at rates greater than chance. © 2012 Elsevier Ltd.